Edible coatings based on cassava starch (manihot esculenta) in vegetable products: a review (Research, Society and Development, 2022)
Biodegradable packaging is edible and has a high potential for contributing to food preservation, polysaccharides have been studied as a component in the production of edible coatings, including cassava starch, for having low cost and good property for the formation of active packaging. Cassava starch has functional properties such as gelatinization, retrogradation, swelling and syneresis that must be controlled in the coating formation process, in order to make it more useful and improve its application, it is necessary that the starch undergoes modifications that can be carried out through chemical, physical, cross-linking, oxidation and substitution methods, including esterification and etherification, pyroconversion. Due to the perishability of hortifruti products, the use of edible coating has become an innovative technology in quality control and increasing the shelf life of these foods. The objective of this work was to review the importance of using cassava starch in the production of edible packaging and its application in products of plant origin in recent years.